Structure of O-Antigen and Hybrid Biosynthetic Locus in Burkholderia cenocepacia Clonal Variants Recovered from a Cystic Fibrosis Patient - Hassan, A.A.; Maldonado, Rita F.; dos Santos, Sandra C.; Di Lorenzo, Flaviana; Silipo, Alba; Coutinho, Carla P.; Cooper, Vaughn S.; Molinaro, Antonio; Valvano, Miguel A.; Sá-Correia, Isabel (Frontiers in Microbiology, 2017)
Burkholderia cenocepacia is an opportunistic pathogen associated with chronic lung infections and increased risk of death in patients with cystic fibrosis. In this work, we investigated the lipopolysaccharide (LPS) of clinical variants of B. cenocepacia that were collected from a cystic fibrosis patient over a period of 3.5 years, from the onset of infection until death by necrotizing pneumonia (cepacia syndrome). We report the chemical structure of the LPS molecule of various sequential isolates and the identification of a novel hybrid O-antigen (OAg) biosynthetic cluster. The OAg repeating unit of the LPS from IST439, the initial isolate, is a [→2)-β-D-Ribf-(1→4)-α-D-GalpNAc-(1→] disaccharide, which was not previously described in B. cenocepacia. The IST439 OAg biosynthetic gene cluster contains 7 of 23 genes that are closely homologous to genes found in B. multivorans, another member of the Burkholderia cepacia complex. None of the subsequent isolates expressed OAg. Genomic sequencing of these isolates enabled the identification of mutations within the OAg cluster, but none of these mutations could be associated with the loss of OAg. This study provides support to the notion that OAg LPS modifications are an important factor in the adaptation of B. cenocepacia to chronic infection and that the heterogeneity of OAgs relates to variation within the OAg gene cluster, indicating that the gene cluster might have been assembled through multiple horizontal transmission events.